The Effect of Liquidity, Leverage, Company Size and Independent Board of Commisioners on Financial Distress - Iswanto, Ochadifa Salsabila; Hariyanto, Eko; Hartikasari, Annisa Ilma (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
Financial distress is a serious problem that threatens the sustainability of the company. The company's financial condition is very important, if the company's finances decline, the company must be prepared to improve the company's financial condition so that financial distress does not occur. This study aims to determine the effect of liquidity, leverage, company size and independent board of commissioners on financial distress. The sampling technique used purposive sampling with a total sample of 64 companies. The population in this study are energy sector mining companies listed on the Indonesia Stock Exchange in 2019-2022. The data used is secondary data. The results showed that liquidity has no effect on financial distress, leverage has a positive effect on financial distress, company size has a negative effect on financial distress, the board of independent commissioners has a positive effect on financial distress.